Mapping Global Research Trends and Directions on the Quiet Quitting Phenomenon: A Bibliometric Analysis in the Context of Human Resource Management - Darmayanto, Darmayanto; Mujanah, Siti; Fianto, Achmad Yanu Alif (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2025)
Mapping Global Research The phenomenon of quiet quitting describes employee behavior in which individuals continue to perform their formal duties while psychologically and emotionally disengaging from the organization. This issue has become more prominent in the post–COVID-19 era, alongside the growing awareness of work-life balance and mental well-being. This study aims to map global research trends and directions related to quiet quitting through a bibliometric analysis of publications indexed in the Scopus database for the 2020–2024 period using the VOSviewer and Biblioshiny tools. The results reveal a significant increase in publications since 2022, highlighting three dominant themes: employee engagement and burnout, work-life balance and mental health, as well as leadership and organizational culture. These findings enrich the Human Resource Management (HRM) literature related to employee engagement and provide insights for developing adaptive HR strategies aligned with evolving work values and modern organizational culture. Keywords: Quiet quitting, bibliometric analysis, employee engagement, work life balance, human resource management.